Influência das variações pluviais nos teores de flúor em águas de poços - Moimaz, Suzely Adas Saliba [UNESP]; Araújo, Paula Caetano [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Sumida, Dóris Hissako [UNESP]; Saliba, Nemre Adas [UNESP] (My University, 2012)
Introduction: The fluoridation surveillance in the public water supply came up with the need to develop mechanisms that would help society in the control of water quality. To perform reliable analysis, variables such as depth of the wells and pluvial variations should be subject of research and study. Objectives: To analyze the fluoride levels of deep wells in periods of rain and drought, corresponding to four brazilian cities and compare the results. Methodology: It was made the mapping of the water supply network and the identification of the sampling points according to the number of deep wells in each locality, selecting those who had the natural fluoride level. Three points were defined for each source of water supply, and the addresses were randomly selected. The samples were analyzed in duplicate at the laboratory of the Center for Research in Public Health of the Dentistry School of Araçatuba – UNESP, during 8 months, in periods of rain and drought (total absence of rain). Results: 174 analysis were conducted, the mean fluoride levels for rain and drought times were, respectively: 0,71 and 0,73. It was used the Student’s t test (p <0.05). Conclusion: There wasn’t statistically significant differences for the periods of rain and drought in any of the cities, at the year of 2010. This study highlights the importance of health surveillance, because beyond of ensuring social control, there is also the search for investigating variables that may have directly and / or indirectly influence on the results of the analysis.

Introdução: A vigilância da fluoretação nas águas de abastecimento público surgiu com a necessidade de desenvolver mecanismos que auxiliem a sociedade no controle da qualidade da água. Para realizar análises fidedignas, variáveis como profundidade dos poços e variação pluviométrica devem ser alvo de pesquisa e estudo. Objetivos: Analisar os teores de flúor de poços profundos correspondentes a 4 municípios brasileiros e comparar os resultados, em períodos de chuva e seca. Metodologia: Foi realizado o mapeamento da rede de abastecimento de água e a identificação dos pontos de coleta de acordo com o número de poços profundos existentes em cada localidade, selecionando aqueles em que o teor de flúor era natural. Foram definidos três pontos para cada fonte de abastecimento de água, sendo os endereços selecionados aleatoriamente. As amostras foram analisadas em duplicata no laboratório do Núcleo de Pesquisa em saúde coletiva da Faculdade de Odontologia de Araçatuba – Unesp, durante 8 meses, considerando períodos de chuva e períodos de seca (ausência total de chuva). Resultados: Foram feitas 174 análises, os teores médios de flúor na época de chuva e seca foram, respectivamente: 0,71 e 0,73. Foi aplicado o teste t de Student (p<0,05). Conclusão: Não houve diferenças estatisticamente significantes para os períodos de chuva e seca no ano de 2010 em nenhum dos municípios. Evidenciase a importância do heterocontrole na vigilância em saúde, pois além de garantir o controle social, busca ainda investigar variáveis que possam influir direta e/ou indiretamente nos resultados das análises.
Influence of pluvial variations in fluoride levels in wells water
Keywords: Wells; Fluoridation; Population surveillance; Health promotion; Poços; Fluoretação; Vigilância da população; Promoção da saúde